Effects of low and high frequency actuation on aerodynamic performance of a supercritical airfoil - Abdolahipour, Soheila (Frontiers in Mechanical Engineering, 2023)
Numerical simulations are conducted to study flow control in a supercritical airfoil with a NASA SC(2)-0714 cross-section using pulsed jet at a chord-based Reynolds number of 1×106. The main objective is to investigate the influence of low- and high-frequency actuation on the aerodynamic performance of the airfoil and its potential application in high-lift or flight control devices. Pulsed jet actuation was implemented on the upper side of the airfoil surface upstream of the separation point of the uncontrolled case using different frequencies of 0.2, 1, 1.2, 2.4, 4, 6, and 12. The aerodynamic efficiency improvements were investigated by extracting the results of time-averaged and instantaneous aerodynamic forces for all cases. The study compared the flow streamline, Q-criterion contour, and surface pressure distribution to examine how separated flow configuration over the airfoil responds to different frequency actuation. The results indicate that pulsed jet actuation effectively postpones flow separation. A comparison of time-averaged aerodynamic coefficients at varying actuation frequencies revealed that utilizing a low actuation frequency range maximizes lift, whereas a high frequency range minimizes drag. Additionally, the aerodynamic efficiency of the supercritical airfoil improves across all controlled scenarios, with the optimal outcome achieved at an actuation frequency of F+=1.